2022
DOI: 10.1210/jendso/bvac147
|View full text |Cite
|
Sign up to set email alerts
|

Acid–Base Imbalance in Pseudohypoaldosteronism Type 1 in Comparison With Type IV Renal Tubular Acidosis

Abstract: Context Pseudohypoaldosteronism (PHA) type 1 (PHA1) has been treated as a genetic variant of type IV renal tubular acidosis (RTA), leading to the conception that PHA1 develops hyperchloremic acidosis with a normal anion gap (AG). Objective To delineate the acid-base imbalance in PHA1A (dominant type) and PHA1B (recessive type). Design We conducted the followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
(37 reference statements)
0
5
1
Order By: Relevance
“…In contrast to the present results, our previous study on PHA1 found that the phenotype was inconsistent with typical hyperchloremic type IV RTA [22]; analysis of data related to seven times well-documented salt-wasting crises experienced by our PHA1B patient between 3 and Endocrine Journal Advance Publication 7 years of age revealed that most of the crises were accompanied by hypochloremia and elevated AG levels. In addition, analysis of 106 PHA1 cases collected through a literature search found that hypochloremia was present in 69% (9 of 13) of PHA1A and 54% (7 of 13) of PHA1B cases at the time of salt-wasting.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to the present results, our previous study on PHA1 found that the phenotype was inconsistent with typical hyperchloremic type IV RTA [22]; analysis of data related to seven times well-documented salt-wasting crises experienced by our PHA1B patient between 3 and Endocrine Journal Advance Publication 7 years of age revealed that most of the crises were accompanied by hypochloremia and elevated AG levels. In addition, analysis of 106 PHA1 cases collected through a literature search found that hypochloremia was present in 69% (9 of 13) of PHA1A and 54% (7 of 13) of PHA1B cases at the time of salt-wasting.…”
Section: Discussioncontrasting
confidence: 99%
“…This fundamental difference in Na + kinetics will cause the opposite direction in the chloride levels between PHA1 (hypochloremic) and PHA2 (hyperchloremic). As we speculate before, an elevated AG found in PHA1 may derive from hyperlacticemia caused by severe volume depletion [22]. Considering that aldosterone unresponsiveness is not the main factor in the pathogenesis of PHA2, it may be thoughtful to treat PHA1 and PHA2 as completely different entities, despite their nomenclature.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Hypochloraemia ([Cl − ] e < 96 mM) is observed in patients with chronic cardiac failure and is associated with higher risk of mortality in patients with acute or chronic heart failure [32,33,34,35]. Hyperchloremia ([Cl − ] e > 110 mM), which accompanies a range of kidney disturbances, is an independent predictor for hypertension [36,37], and positively associated with increased mortality rate of hospitalised patients [34]. These conditions are expected to impact E Cl and thus the magnitude of TMEM16A currents.…”
Section: Chloride Homeostasis In Vascular Cellsmentioning
confidence: 99%